Toll-like receptor 2 and 4 polymorphisms associated with Helicobacter pylori susceptibility and gastric cancer - , Taweesak Tongtawee, Theeraya Simawaranon, Wareeporn Wattanawongdon, Chavaboon Dechsukhum, Wilairat Leeanansaksiri (Turkish Journal of Gastroenterology 1, 2019)
Background/Aims: Genetic polymorphisms in Toll-like receptors (TLRs) are important influence on gastric lesion development and Helicobacter pylori susceptibility. Materials and Methods: TLR2 rs3804099 and rs3804100 and TLR4 rs10759932 were determined in a total of 400 patients. The association among genotypes and the risk of gastric lesion development and H. pylori susceptibility were evaluated by the odds ratios (ORs) and 95% confidence intervals (95% CIs) from logistic regression analyses. Results: TLR4 rs10759932, C/C homozygous genotype was associated with an increased risk of premalignant/malignant (OR=2.48, 95% CI=1.96-4.62, p=0.015). The recessive model of TLR4 rs10759932 showed a decreased risk of H. pylori susceptibility (adjusted OR=0.52, 95% CI=0.38-0.82, p=0.046). Meanwhile, the recessive model was associated with an increased risk of non-malignant (OR=3.46, 95% CI=2.25-5.67, p=0.001). In subjects with H. pylori infection, the recessive model was associated with an increased risk of non-malignant (OR=2.28, 95% CI=1.24-3.57, p=0.001) and premalignant/malignant (OR=1.83, 95% CI=1.16-2.84, p=0.027). Conclusion: TLR4 rs10759932, but not TLR2 rs3804099 and rs3804100, was associated with risk of premalignant and/or malignant and H. pylori susceptibility. H. pylori infection seems to contribute to chronic gastritis, and premalignant/malignant supported the development of the premalignant/malignant lesions involved in H. pylori infection that is critical to gastric cancer in Thai patients. Cite this article as: Tongtawee T, Simawaranon T, Wattanawongdon W, Dechsukhum C, Leeanansaksiri W. Toll-like receptor 2 and 4 polymorphisms associated with Helicobacter pylori susceptibility and gastric cancer. Turk J Gastroenterol 2019; 30: 15-20.